Effect of temperature and social environment on worker size in the ant Temnothorax nylanderi. (July 2017) - Molet, Mathieu; Péronnet, Romain; Couette, Sébastien; Canovas, Christophe; Doums, Claudie
Abstract: Warm temperatures decrease insect developmental time and body size. Social life could buffer external environmental variations, especially in large social groups, either through behavioral regulation and compensation or through specific nest architecture. Mean worker size and distribution of worker sizes within colonies are important parameters affecting colony productivity as worker size is linked to division of labor in insect societies. In this paper, we investigate the effect of stressful warm temperatures and the role of social environment (colony size and size of nestmate workers) on the mean size and size variation of laboratory-born workers in the small European ant Temnothorax nylanderi . To do so, we reared field-collected colonies under medium or warm temperature treatments after having marked the field-born workers and removed the brood except for 30 first instar larvae. Warm temperature resulted in the production of fewer workers and a higher adult mortality, confirming that this regime was stressful for the ants. T. nylanderi ants followed the temperature size rule observed in insects, with a decreased developmental time and mean size under warm condition. Social environment appeared to play an important role as we observed that (i) larger colonies buffered the effect of temperature better than smaller ones (ii) colonies with larger workers produced larger workers whatever the rearing temperature and (iii) the coefficient of variation of worker size was similar in the field and under medium laboratory temperature. This suggests that worker size variation is not primarily due to seasonal environmental fluctuations in the field. Finally, we observed a higher coefficient of variation of worker size under warm temperature. We propose that this results from a disruption of social regulation, i.e. the control of nestmate workers over developing larvae and adult worker size, under stressful conditions. Graphical abstract: Highlights: Temperature affects the size and size variance of workers produced by ant colonies. Under warmer temperature, colonies produce smaller workers. Under warmer temperature, colonies produce workers that are more variable in size. Stressful warm temperatures can disrupt the social regulation of worker size.